THE JEAN MONNET PROGRAMME AS AN INSTRUMENT OF EDUCATION FOR DEMOCRACY - Dybowska, Agnieszka (Management and Administration Journal, 2024)
The Maastricht Treaty introduced the concept of European Union citizenship, providing additional rights for European citizens. The EU has given its citizens the opportunity to participate and engage in politics, as well as the additional right to vote, but has not focused on investing in citizenship education that would give citizens the knowledge and skills necessary to exercise these newly acquired rights. So far, EU education policy has focused mainly on employability and access to the labor market. The discussion on citizenship education at European level has been quite lively. According to the documents examined, the evaluation of education for democracy in the European Union is low, but the evaluation of the Erasmus+ program in civic education is positive. This article is the result of research on the use of European Union programs, in particular the Jean Monnet Programme in education for democracy.